The Effect of English Training Course To English Learning Achievement For C Package Students of Learning Activity Group (SKB) Tegal Municipality - Nur Laila Molla (Cakrawala: Jurnal Pendidikan, 2018)
The purpose of this research is to know the interest to join English language training for students of Learning Activity Group (SKB) Tegal Municipality Package C. The population of this research is students C Package SKB Tegal Municipality academic year 2017/2018. The population is twenty. This research was conducted using one sample. The sample is taught English course training. Type of research is Experimental. Instruments used in this research are questionnaire and test. After English training for sixteen meetings, participants were asked to fill in questionnaire sheet, where statement item in questionnaire ranged from measuring the interest of sample to English training they joined. Data analysis of this research was tested using a t-test to determine whether Hypothesis was accepted or not. Based on the calculation that t-count is 0.444 compared with t-table at 5% significance level and freedom level (df) is 19. From calculation data obtained that t-count> t-table is 0.641> 0.444. Therefore, it is concluded that hypothesis of the research is accepted. The conclusion of this research is that there is an increasing influence of interest to participate in English Language Skills Training to the Interest of Learning English for students of C Package SKB Tegal Municipality. Advice that can be given by the researcher is the English teacher is suggested to give English Training to SKB students, especially C Package students or equivalent of Senior High School.